2004
DOI: 10.1002/anie.200460941
|View full text |Cite
|
Sign up to set email alerts
|

Activation of an Autoregulated Protein Kinase by Conditional Protein Splicing

Abstract: The temporal and spatial control of protein function is of fundamental importance in biology. Most cellular processes require that a small subset of the proteome be active at a particular time and place, and that this activity have a defined duration. To probe the role of a protein in a biological system, one must be able to control these parameters as precisely as possible. [1,2] We recently developed a new tool, termed conditional protein splicing (CPS), to control the primary structure, and hence function, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 22 publications
(27 reference statements)
2
26
0
Order By: Relevance
“…SURF represents an attractive alternative when the protein of interest is known to take part in protein-protein interactions or multimeric complexes as rescue is inextricably linked to generation of the native protein. In the future this cleavage-dependent rescue technology could be expanded to include other methods of protein regulation such as mislocalization or autoinhibition (34).…”
Section: Discussionmentioning
confidence: 99%
“…SURF represents an attractive alternative when the protein of interest is known to take part in protein-protein interactions or multimeric complexes as rescue is inextricably linked to generation of the native protein. In the future this cleavage-dependent rescue technology could be expanded to include other methods of protein regulation such as mislocalization or autoinhibition (34).…”
Section: Discussionmentioning
confidence: 99%
“…Although natural inteins splice spontaneously, inteins that undergo splicing in a small-molecule-dependent manner have been developed by fusing intein halves with proteins that dimerize in the presence of a small molecule (Mootz and Muir, 2002; Mootz et al, 2003; Shi and Muir, 2005), or by directed evolution in which a library of intact inteins fused to a ligand-binding domain was screened to splice in the presence, but not the absence, of a small molecule (Buskirk et al, 2004). These small-molecule-dependent inteins have enabled protein function in cells to be controlled post-translationally by the addition of an exogenous, cell-permeable molecule (Mootz and Muir, 2002, Mootz et al, 2003, Buskirk et al, 2004; Mootz et al, 2004; Shi and Muir, 2005; Yuen et al, 2006; Schwartz et al, 2007; Hartley and Madhani, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…This has allowed the development of so-called conditional protein splicing systems in which the splicing reaction is triggered by induced proximity of the intein fragments through either the use of small molecule or light stimulation. [31][32][33] We have shown that conditional protein splicing can be used to for the rapid and tunable activation of proteins in a variety of cell types 34 and even in a living animal. 35 …”
Section: Protein Splicingmentioning
confidence: 99%